The parole performance of offenders released from shock incarceration (boot camp prisons): A survival time analysis - MacKenzie, Doris L. (Journal of quantitative criminology, 1991)
The parole performance of offenders who were released after successfully completing a shock incarceration program was examined and compared to the performance of offenders who were serving time on probation or parole after a period of incarceration. Separate survival analyses were performed for recidivism as measured by (1) arrests and (2) failures (jailed, absconded, or revoked). Prior incarceration, age, age at first arrest, and risk assessment score were related to recidivism but type of sentence was not. Intensity of supervision was significantly related to recidivism but this relationship was eliminated when risk level was controlled. There was no evidence that shock incarceration reduces recidivism. Future research should focus on methods of reducing failures during community supervision for these young, nonviolent offenders within the framework of either a shock incarceration program or some other sentence.